Culture as one of the Determinants of Church and State Legislation: A Case of Canon Law - Kroczek, Piotr (Philosophy and Canon Law, 2020)
The aim of this article is to show how culture influences church legislation and to identify possible dangers associated with it. The article illustrates examples of changes in Church law that take place under the influence of culture. The conclusions are as follows: canon law submits to culture and it is a possible threat because it loses its ecclesiastical and salvific character. The legislator should be aware of such a phenomenon and try to preserve specific features, especially the purpose of canon law.